Low T-Cell Receptor β (TRB) Repertoire Diversity Early Post-Transplant for Severe Combined Immunodeficiency (SCID) Predicts Subsequent Failure of Immune Reconstitution - Delmonte, Ottavia Maria; Castagnoli, Riccardo; Chang, Catherine K.; Dela Cruz, Melanie; Yu, Jason; Dvorak, Christopher C.; Chandra, Sharat; Davila, Blachy; Cowan, Morton J.; Notarangelo, Luigi D.; Puck, Jennifer (Biology of blood and marrow transplantation, 2020)
Development of a diverse T cell repertoire is associated with immune recovery following allogeneic hematopoietic cell transplantation (HCT) for SCID. Although CDR3 spectratyping and staining of Vβ families provide approximations of the diversity of T cell receptors, high-throughput sequencing (HTS) of the TRB repertoire allows precise evaluation of clonotype dynamics during immune reconstitution. We investigated whether longitudinal HTS analysis of TRB would accurately assess development of TCR repertoire diversity over time and reflect the quality of T cell reconstitution following HCT for SCID. We also studied the influence of SCID genotype, conditioning regimen, donor type, and occurrence of chronic graft versus host disease (cGVHD) on TCR diversity post HCT. We hypothesized that repertoire diversity may represent an early biomarker to predict long-term immune reconstitution vs. need for a second intervention. HTS was used to study the composition and diversity of TRB repertoire of 27 SCID infants, pre-HCT and at 100 d, 6 and 12 mo and yearly post-treatment(s). Median time of follow-up was 48 mo. Subjects were part of a prospective study of SCID by the Primary Immunodeficiency Treatment Consortium. Equal amounts of total RNA extracted from peripheral blood was used as template to amplify TRB rearrangements. The VDJ statistics file (PAST program) was used to calculate a Shannon entropy (H) index to measure repertoire diversity. TRB sequence analysis of 27 SCID patients showed poor diversity at baseline, followed by improvement to normal complexity (H index >8.0) after HCT. Similar kinetics of development of TRB diversity were seen in patients with IL2RG, JAK3, and IL7R defects (n=16) as in those with RAG and Artemis defects (n=14). In the latter group, however, HCT with no conditioning or immune suppression only was associated with persistently lower diversity than HCT with conditioning (p<0.01), a difference not found in the IL2RG/JAK3/IL7R group. HCT from a matched donor (6/13 conditioned) correlated with higher diversity than HCT from a mismatched donor (5/15 conditioned) (p=0.01). Having > 500 CD4+ T cells/ul or > 200 naïve CD4+ T cells/ul at 6 mo post-HCT correlated with higher TRB diversity at 24 and 36 mo post-HCT (p<0.01). An H-index of 4.7 or lower at 100 d after HCT predicted need for second intervention (HCT or GT) with 92% sensitivity and 100% specificity. cGVHD (n=4) did not affect diversity in this cohort. Analysis of TRB diversity permits a detailed assessment of development of a diverse T cell repertoire following cellular therapies for SCID and confirms the need for patient-tailored treatment strategies based on SCID genotype. We propose that analysis of TRB diversity at 100 d post-HCT may identify patients at risk for failure of sustained immune reconstitution, thus prompting a second intervention without delay.